2021
DOI: 10.1016/j.ajpath.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Novel Functions of the Septin Cytoskeleton

Abstract: Chronic inflammatory diseases cause profound alterations in tissue homeostasis, including unchecked activation of immune and nonimmune cells leading to disease complications such as aberrant tissue repair and fibrosis. Current anti-inflammatory therapies are often insufficient in preventing or reversing these complications. Remodeling of the intracellular cytoskeleton is critical for cell activation in inflamed and fibrotic tissues; however, the cytoskeleton has not been adequately explored as a therapeutic ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 115 publications
(176 reference statements)
0
11
0
Order By: Relevance
“…The human septin family contains 14 genes (SEPT1-SEPT14), encoding dozens of different septin proteins. Among them, SEPT9 encodes a GTP-binding protein, which plays a role in cytokinesis, intracellular material transport, cell cycle regulation, and apoptosis ( Ivanov et al, 2021 ). Wu et al (2017) found that SEPT9 is hypermethylated in TGF-β1-treated mouse HSCs and CCl 4 -treated mouse liver, and SEPT9 protein expression is significantly reduced, leading to increased ECM accumulation and aggravated fibrosis compared with that in controls.…”
Section: Liver Fibrosis-related Genes and Dna Methylationmentioning
confidence: 99%
“…The human septin family contains 14 genes (SEPT1-SEPT14), encoding dozens of different septin proteins. Among them, SEPT9 encodes a GTP-binding protein, which plays a role in cytokinesis, intracellular material transport, cell cycle regulation, and apoptosis ( Ivanov et al, 2021 ). Wu et al (2017) found that SEPT9 is hypermethylated in TGF-β1-treated mouse HSCs and CCl 4 -treated mouse liver, and SEPT9 protein expression is significantly reduced, leading to increased ECM accumulation and aggravated fibrosis compared with that in controls.…”
Section: Liver Fibrosis-related Genes and Dna Methylationmentioning
confidence: 99%
“…This analysis uncovered several plasma proteins significantly associated with combined asthma‐atopy phenotypes but not with asthma overall, including septin‐6 (SEPT6). Septins play a crucial role in inflammation and have potential in therapeutic treatments 64 …”
Section: Discussionmentioning
confidence: 99%
“…Septins play a crucial role in inflammation and have potential in therapeutic treatments. 64 A recent study of asthma genetics implicated 174 genes. 65 Of these, one (IL4R) was associated with asthma in our data.…”
Section: Discussionmentioning
confidence: 99%
“…The main challenge of studying the septin’s biology is the complexity of septins. In mammals, there are 13 septin genes and at least 11 pseudogenes, coding for transcripts and proteins with extensive posttranscriptional modifications and alternative splicing isoforms ( 14 ). Moreover, septin’s biology is very complex because septins are evolutionary old and present in divergent eukaryotic lineages, including algae and ciliates ( 15 ).…”
Section: Introductionmentioning
confidence: 99%